(3GddBdF hGdOQQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi aEf GdbGVi GdLdjd GdSjO hbSeJg ai YTQI CHhGH GdHGH GdChd ai HYV eG fWb GdbQBf GdYXje ef GdcdGe GdYXje ef CQGO Cf jYQa LhGeY Gdcde s
(3BNQgG (B:s
(3bhdg cJH ef aRW hcag cGdMdeg hCTZdg HPi s
(3Vef eLehY , JQJjHgG (B: 1(3GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs